Fa’aliyat TathbIq Lu’bah Froggy Jump li Tarqiyah Ta’lim Maharat al-Qira’ah: bahtsu Tajribiy/The Effectiveness of Using Froggy Jump Game to Improve Reading Skills: An Experimental Study - Via Aulia; Mu'at Mu'at (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
The "Froggy Jump" game makes it easier for students to follow and understand the lesson, encouraging them to improve their reading skills. Through this medium, students can easily express their understanding of the reading material. This quantitative approach employs a type of experimental research, where the experimental research includes a treatment (intervention). In a one-group pretest-posttest design, the dependent variable is measured as a single group; the pre-test and post-test are given with the treatment in between. As for the research results: the application of the "Froggy Jump" game helped students understand vocabulary, identify the main idea, and answer questions based on context. This application helped enhance students' understanding and motivation, as the game became an effective interactive tool in teaching reading skills. The effectiveness of using the "Froggy Jump" game led to a significant change in students' reading skills. Most students initially had low scores, and the t-test results showed that the significance value (Sig. = 0.00) was less than 0.05, indicating a statistically significant difference in reading skills.إن لعبة "Froggy Jump" تسهل على الطلاب المتابعة وفهم الدرس وذلك لتشجيع الطلاب لترقية تعليم مهارة القراءة. من وسائل هذه الوسائط، يمكن للطلاب التعبير بسهولة عن القراءة. استخدامت هذه المدخل الكمية بنوع من البحث التجريبي، حيث يتضمن البحث التجريبي وجود معالجة (تدخل)، في تصميم الاختبار اللاحق للمجموعة الواحدة، يتم قياس المتغير المرتبط كمجموعة واحدة الاختبار القبلي والاختبار البعدي يتم إعطاء العلاج. أما نتائج البحث: تطبيق لعبة "Froggy Jump" حصل الطلاب فهم المفردات، وتحديد الفكرة الرئيسة، والإجابة عن الأسئلة بناء على السياق. ساعد هذا التطبيق في تعزيز فهم الطلاب وتحفيزهم، حيث أصبحت اللعبة وسيلة تفاعلية فعّالة في تعليم مهارة القراءة. وفعالية استخدام لعبة "Froggy Jump" بالنسبة إلى نتائج تغيير كبير في مهاراة القراءة لدى الطلاب حصل معظم الطلاب على درجات منخفضة، وأظهرت نتائج اختبا t أن قيمة الدلالة (Sig. = 0.00) كانت أقل من 0.05، مما يدل على وجود فرق ذي دلالة إحصائية في مهارة القراءة.